The development and the use of clearing house server infrastructure for gis interoperabilty - Nanna Suryana, Herman; Norayu, Abdul Ghani (2006)
Rapid development of internet technology allows more spatial and tabular data available and accessible publicly. But those data can not be utilized directly due to the differences in data acquisition techniques, data definition and their semantic meaning. This situation reveals the need of interoperable GIS to support seamless information sharing. This is the future GIS architecture that may increase the reusability of available spatial datasets and reduce data acquisition cost. Under the whole framework of the on going research has identified four components (modules) to support the application of GJS interoperability. This paper discusses the development and the use of clearinghouse component (module) to facilitate end users to search, locate and retrieve the required spatial information or meta data from different organization at different time and places. This allows making further enquire about particular spatial data-information. The detail discussions on GIS Interoperability model as well as the development of architecture of these clearinghouse servers are given. The development of clearing house server employs an open sources approach and open file format. In this regards, fully available source code allows modification and customization without licensing restrictions.